“Our hopes and dreams enrich its every corner” : Adult Education with an Africentric Focus - Susan M. Brigham (Adult Education Research Conference, 2007)
This paper addresses the ways in which Africentricity contributes to adult education’s goal of creating a socially just world and specifically to a graduate adult education/lifelong learning degree program within a Nova Scotian university context.